Glycaspis brimblecombei moore, "Psilido de los eucaliptos rojos" (Hemiptera: Psyllidae: spondyliaspidinae): caracteres taxonomicos. - Olivares, T.S.=700 1 Burckhart, D.H.; Cerda, L.A.
(En, Es)
ilus., 12 ref.
Keywords: TAXONOMIA; PSYLLIDAE; HEMYPTERA; EUCALYPTUS CAMALDULENSIS; CHILE; SPONDYLIASPININAE; GLYCAPSIS